Development of the method going to the decisionmaking in relation to carriage-cistern with the past appointed tenture of employment in the conditions of completion of the third stage of life cycle - Voropaj, V. S. (Science and Transport Progress, 2012)
The article is sanctified to the questions of maintenance of a worker park of carriages-cisterns which have settled the appointed resource . The method which supposes well-founded choice between prolongation(by the extension of time of service), by acquisition of new unit of rolling stock or utilization of carriage-cistern is offered.